Solitary intracerebral Langerhans cell histiocytosis - Shanthi Vissa; Aruna Kumari Prayaga; Swathi Bontha; Rukmangadha Nandyala; Ramesh Chandra; VeeraSekhar Kattela (Romanian Neurosurgery, 2024)
Background: Langerhans cell histiocytosis is an uncommon proliferative histiocytic disorder which can affect any organ. It is common in children and can rarely occur in adults. In the central nervous system, the hypothalamic-pituitary axis is most commonly involved. Brain parenchyma is rarely affected.